Facile de Novo Sequencing of Tetrazine‐Cyclized Peptides through UV‐Induced Ring‐Opening and Cleavage from the Solid Phase. (4th January 2023) - Borges, Ariane; Nguyen, Chi; Letendre, Madison; Onasenko, Iryna; Kandler, Rene; Nguyen, Ngoc K.; Chen, Jue; Allakhverdova, Tamara; Atkinson, Emily; DiChiara, Bella; Wang, Caroline; Petler, Noa; et al.
Abstract: While most FDA‐approved peptide drugs are cyclic, the robust cyclization chemistry of peptides and the deconvolution of cyclic peptide sequences by using tandem mass spectrometry render cyclic peptide drug discovery difficult. Here we present the successful design of cyclic peptides on solid phase that addresses both of these problems. We demonstrate that this peptide cyclization method using dichloro‐ s ‐tetrazine on solid phase allows successful cyclization of a panel of random peptide sequences with various charges and hydrophobicities. The cyclic peptides can be linearized and cleaved from the solid phase by simple UV light irradiation, and we demonstrate that accurate sequence information can be obtained for the UV‐cleaved linearized peptides by using tandem mass spectrometry. The tetrazine linker used in the cyclic peptides can further be explored for inverse electron‐demand Diels‐Alder (IEDDA) reactions for screening or bioconjugation applications in the future. Abstract : The successful design and synthesis of solid‐phase‐bound monocyclic peptides with various charges and hydrophobicity are presented. The design allows the bead‐bound peptides to be linearized and cleaved from the solid phase by a single‐step UV irradiation, allowing facile sequence identification by using tandem mass spectrometry.